Chemical Parameters of Oxidative Stress Adaptability in Beech - D. Štajner; S. Orlović; B. M. Popović; M. Kebert; S. Stojnić; B. Klašnja (Journal of Chemistry)
The antioxidant activity, lipid peroxidation, and contents of free proline and soluble proteins were investigated on six-year-old beech plants. Provenance Avala, in Serbia, had the best adaptability to environmental factors on locality Fruska Gora due to low lipid peroxidation, high FRAP value, and free proline and soluble proteins contents. Provenances Scharnstein and Mitterndorf, in Austria, had the best adaptability to environmental factors on locality Debeli Lug due to high FRAP value and free proline and soluble proteins contents. FRAP values in majority of provenances from locality Debeli Lug were higher. Correlations parameters were much higher between provenances in locality Debeli Lug, situated at higher altitude, which is the consequence of better adaption to environmental factors influence.